Employee Mental Health Can Moderate the Effect of Work Motivation on Employee Performance - Rieneke Ryke Kalalo; Teguh Setiawan Wibowo; Arif Ismundandar; Hasrul Edyar; Ida I Dewa Ayu Raka Susanty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the dynamic and stressful modern corporate era, organizational productivity is highly dependent on optimizing human resource potential. This study aims to analyze and examine the role of employee mental health as a moderating variable in the relationship between work motivation and employee performance. Using a quantitative approach with a survey method, data were collected from a sample of industrial sector employees experiencing high levels of work stress. Data analysis was conducted using Moderated Regression Analysis (MRA) to detect the interaction effects of the moderating variables. The results of the analysis indicate that work motivation has a positive and significant influence on employee performance. However, testing for the moderation effect proves that this positive relationship is significantly strengthened when employees have a high level of mental health. Conversely, in conditions of poor mental health, the effect of motivation on performance decreases drastically. These findings confirm that conventional motivation enhancement programs will not achieve optimal results if organizations ignore workers' psychological well-being. The practical implications of this study urge company management to integrate mental health programs into human resource development strategies to maintain sustainable organizational performance.